The Relationship between Characteristics with Medication Adherence and Quality of Life among the Pulmonary Tuberculosis Patients at the Cirebon City Community Lung Health Center, Indonesia - Asri Permata Dewi; Niklah Zaidah; Sri Marfuati (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Tuberculosis (TB) is one of the top ten causes of death worldwide, caused by the Mycobacterium tuberculosis germ. Adherence to medication is a key factor in successful treatment and efforts to improve the quality of life of TB patients. Aims: Analyzing the relationship between characteristics with medication adherence and quality of life of pulmonary TB patients at the Cirebon City Community Lung Health Center. Methods: This study used an analytic observation method with a Cross Sectional design. The measuring instruments used were medical records and questionnaires that had been tested for validity and reliability, with a total of 131 respondents of pulmonary TB patients at the Cirebon City Community Lung Health Center (BKPM). Results : The most common characteristics were adult age 90.8%, female gender 56.5%, secondary education 50.4%, student 28.2%, length of treatment at the advanced stage 59.5%, adherent to taking medication 87.0%, good quality of life 54.2%. Based on the Chi-Square test, the relationship between characteristics and drug compliance from age p-value=0.189, gender p-value=0.320, education p-value=0.447, occupation p-value=0.594, length of treatment p-value=0.014. The relationship between characteristics and quality of life from age p-value=0.688, gender p-value=0.550, education p-value=0.838, occupation p-value=0.519, length of treatment p-value=0.604. Based on the logistic regression test, the relationship between characteristics and drug compliance from age p-value=0.058, length of treatment p-value=0.006. Conclusion: There is no relationship between age, gender, education, and occupation with medication adherence (p>0.05). Whereas in the length of treatment there is a relationship with adherence to taking medication. There is no relationship between characteristics and quality of life of pulmonary TB patients (p>0.05). The characteristic most associated with adherence to taking medication is length of treatment (p=0.006). Future researchers are advised to explore other factors that may be related to medication adherence and quality of life in patients with pulmonary TB.